2015
DOI: 10.1126/science.1259038
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic profiling of the protein life cycle in response to pathogens

Abstract: Protein expression is regulated by production and degradation of mRNAs and proteins, but their specific relationships remain unknown. We combine measurements of protein production and degradation and mRNA dynamics to build a quantitative genomic model of the differential regulation of gene expression in LPS-stimulated mouse dendritic cells. Changes in mRNA abundance play a dominant role in determining most dynamic fold changes in protein levels. Conversely, the preexisting proteome of proteins performing basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
484
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(532 citation statements)
references
References 71 publications
45
484
3
Order By: Relevance
“…Comparison with previously generated full-length libraries generated by the same laboratory, using the same protocol at two different times (Garber et al 2012;Jovanovic et al 2015), showed that the difference between end-sequence and full-length libraries was similar to the difference between full-length libraries from biological replicates made by different people at different times (Supplemental Fig. S2).…”
Section: Accurate Mapping Of End-sequence Libraries Presents Unique Cmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparison with previously generated full-length libraries generated by the same laboratory, using the same protocol at two different times (Garber et al 2012;Jovanovic et al 2015), showed that the difference between end-sequence and full-length libraries was similar to the difference between full-length libraries from biological replicates made by different people at different times (Supplemental Fig. S2).…”
Section: Accurate Mapping Of End-sequence Libraries Presents Unique Cmentioning
confidence: 99%
“…Alternative promoter and polyadenylation usage are two key mechanisms by which expression can be controlled transcriptionally or post-transcriptionally (Elkon et al 2013;de Klerk and 't Hoen 2015). Although the response of mBMDCs to LPS has been extensively characterized (Amit et al 2009;Garber et al 2012;Rabani et al 2014;Jovanovic et al 2015), the exact contribution of these two mechanisms to the transcriptional response to LPS is largely unknown.…”
Section: A Methods Specifically Designed For End-sequence Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, extracellular RNAs, especially microRNAs, as well as long non-coding RNAs may also be of diagnostic utility [9,10]. Finally, recent analysis of the relative global importance of transcriptional and translational regulation of protein expression has suggested that the former has been underestimated in prior work and that transcriptional regulation accounts for a large majority of variation in the expressed genome, reinforcing the importance of examining RNA levels [11][12][13].…”
mentioning
confidence: 99%